2011
DOI: 10.1371/journal.pone.0022129
|View full text |Cite
|
Sign up to set email alerts
|

GATA6 Activates Wnt Signaling in Pancreatic Cancer by Negatively Regulating the Wnt Antagonist Dickkopf-1

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a highly lethal disease characterized by late diagnosis and treatment resistance. Recurrent genetic alterations in defined genes in association with perturbations of developmental cell signaling pathways have been associated with PDAC development and progression. Here, we show that GATA6 contributes to pancreatic carcinogenesis during the temporal progression of pancreatic intraepithelial neoplasia by virtue of Wnt pathway activation. GATA6 is recurrently amplified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
82
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 42 publications
3
82
2
Order By: Relevance
“…Finally, TWIST1 can be directly targeted for upregulation by STAT3 (Qin et al, 2012), an important driver of CTCL pathogenesis . Similarly, overexpression of GATA6 has been implicated in oncogenesis by increasing the Wnt signaling pathway (Zhong et al, 2011). Finally, a recent study suggested that PLS3 overexpression confers anti-apoptotic properties to T cells along with an increase in their migration properties (Begue et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Finally, TWIST1 can be directly targeted for upregulation by STAT3 (Qin et al, 2012), an important driver of CTCL pathogenesis . Similarly, overexpression of GATA6 has been implicated in oncogenesis by increasing the Wnt signaling pathway (Zhong et al, 2011). Finally, a recent study suggested that PLS3 overexpression confers anti-apoptotic properties to T cells along with an increase in their migration properties (Begue et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…21 The TGFβ and HH/GLI pathway are coordinately expressed in many developmental processes. In pancreatic cancer, this normal regulation is disrupted by abnormal functioning of the TGFβ pathway, and GLI1 becomes a subverted downstream target of the oncogenic KRAS.…”
mentioning
confidence: 99%
“…5). GATA6 is reported to be an oncogene in various cancers such as colon (18), pancreatic (19) or colorectal cancer (28), but the function of GATA6 in liver cancer is still elusive. The current study showed direct involvement of GATA6 in miR-143-mediated HCC regulation, suggesting that GATA6 also serves an oncogenic function in HCC, which may be related to miRNA dysregulation.…”
Section: Discussionmentioning
confidence: 99%
“…GATA-binding factor 6 (GATA6) has previously been described as a transcriptional factor with a zinc finger structure, which serves as an oncogenic factor in various types of tumor (17)(18)(19). For instance, it has been demonstrated that GATA6 can favor cancer progression by activating Wnt signaling in pancreatic cancer (17,19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation